Evaluation of the load system produced by a single intrusion bend in a maxillary lateral incisor bracket with different alloys - Shintcovsk, Ricardo Lima; Silva Junior, Roberto Soares da [UNESP]; White, Larry; Martins, Lidia Parsekian [UNESP]; Martins, Renato Parsekian [UNESP] (E H Angle Education Research Foundation, Inc, 2018)
Objectives: To evaluate if a 0.5-mm vertical bend applied on an incisor bracket produces movements in other planes and if different wires influence these effects. Materials and Methods: An acrylic model of a treated patient with brackets passively bonded was attached to an Orthodontic Force Tester, and a load cell was attached to the left lateral incisor. Thirty 0.019 x 0.025-inch archwires were divided into three groups according to their alloy: SS (stainless steel), B-Ti (beta-titanium), and MF (beta-titanium wire coated with nickel-titanium). Step-bends of 0.5 mm high were placed on the lateral incisor bracket using a universal plier, and the forces and moments in three dimensions were statistically analyzed by analysis of variance and Tukey post hoc test. Results: SS produced a larger force (3.4 N) than the B-Ti (1.41 N) and the MF (0.53 N; P < .001). Lingual forces were produced by the SS (0.82 N) and B-Ti (0.31 N) groups, while in the MF group, the force was insignificant. SS produced a mesial force of 0.24 N, while the B-Ti force was insignificant and MF produced 0.09 N. Groups produced different crown-distal tipping moments (SS 31.48 N-mm, B-Ti 11.7 N-mm, and MF 4.55 N-mm) and different crown-buccal tipping moments. SS produced larger moments (3.63 N-mm) than B-Ti (1.02 N-mm) and MF (0.36 N-mm) wires. A mesial-out rotational moment was observed in all groups (SS = 7.17 N-mm, B-Ti = 3.46 N-mm, and MF = 0.86 N-mm). Conclusions: A 0.5-mm intrusion bend produced lingual and mesial side effects. In addition to the distal and buccal crown-tipping moments, there was a mesial-out moment. Compared with SS, B-Ti and MF wires produced lower forces. These more flexible wires showed side effects with lesser intensity.
Keywords: Bends; Intrusion; Mechanics